Antara Syar'i dan 'Spill': Bagaimana Konten Dakwah Fashion di Media Sosial Membentuk Perilaku Konsumtif Mahasiswi Pendidikan Agama Islam? - Rohmatin, Alfa; Ridwan, Endan Hamdan; Gandara, Tedi; Permana, Diansyah; Masitoh, Imas (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2025)
Introduction: The proliferation of dakwah fashion content on social media, driven by influencers, has created a cultural paradox where Islamic values intersect with consumerism. While this phenomenon is assumed to influence purchasing decisions, its actual impact on individuals who are religiously educated remains empirically under-researched. This study aims to analyze the influence of social media usage intensity and dakwah fashion influencers on the consumption behavior of female Islamic Education (PAI) students in Indonesia. Methods: A quantitative approach was employed, using a total sampling method (census) to involve 50 active female students from the PAI program at STIT Al-Azami Cianjur. Data were collected through a structured questionnaire with a five-point Likert scale and analyzed using multiple linear regression, including classical assumption tests. Results: The statistical analysis yielded a counterintuitive yet significant outcome. The findings indicate that neither the intensity of social media usage nor the influence of dakwah fashion influencers had a statistically significant effect, either partially or simultaneously, on the students' consumptive behavior (p > 0.05). The model’s coefficient of determination (R-Square) was also extremely low, confirming a weak explanatory power. Conclusion and suggestion: This study concludes that female PAI students exhibit a form of "critical immunity" to the commercial persuasion embedded in dakwah fashion content. It is argued that their formal religious education fosters a critical religious literacy, enabling them to separate aesthetic appreciation from consumptive action. These findings challenge the generalized assumption of influencer power and underscore the necessity of segmenting Muslim consumers not just by piety, but by their level of critical religious education. Future qualitative research is recommended to explore the cognitive mechanisms behind this immunity. Keywords: Consumptive Behavior, Dakwah Fashion, Influencer, Islamic Education Student, Social Media.